2017
DOI: 10.3390/w9070539
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Emissions from the Littoral Zone of a Chinese Reservoir

Abstract: Abstract:The continuous increase in the number of reservoirs globally has raised important questions about the environmental impact of their greenhouse gases emissions. In particular, the littoral zone may be a hotspot for production of greenhouse gases. We investigated the spatiotemporal variation of CO 2 flux at the littoral zone of a Chinese reservoir along a wet-to-dry transect from permanently flooded land, seasonally flooded land to non-flooded dry land, using the static dark chamber technique. The mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
3
1
Order By: Relevance
“…Moreover, 10°C warming failed to stimulate ETzone CO 2 emission signi cantly, while signi cantly stimulated that in the upper aerobic surface and anaerobic deep soil in the conditions of pristine eld. In contrast with most other ndings labeling ETzone as a hotspot in the ecosystem 1,4,5,34 , the lowest CO 2 emission rate and least warming response of the ETzone at the subsurface of peatland in our study showed that it was inert and resistant to warming. Such phenomenon can be explained by the constitution and characteristics of the carbon at ETzone soil.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, 10°C warming failed to stimulate ETzone CO 2 emission signi cantly, while signi cantly stimulated that in the upper aerobic surface and anaerobic deep soil in the conditions of pristine eld. In contrast with most other ndings labeling ETzone as a hotspot in the ecosystem 1,4,5,34 , the lowest CO 2 emission rate and least warming response of the ETzone at the subsurface of peatland in our study showed that it was inert and resistant to warming. Such phenomenon can be explained by the constitution and characteristics of the carbon at ETzone soil.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition to warming, hydrologic changes associated with climate change might affect those C fluxes. Yang et al [30] quantified emissions of CO 2 from the littoral zone of a reservoir in Beijing, China, taking measurements with a dark chamber and gas chromatography techniques along a transect from a permanently flooded location to a seasonally flooded location and then to dry land. They also compared emissions from places with different vegetation types within each hydrographic band.…”
Section: Changes In Hydrology and Land Usementioning
confidence: 99%
“…To investigate the thermal stratification structure in the reservoir, a thermometer chain was installed at R4, and continuous water temperature monitoring was performed at given water depths. Water thermometers (HOBO Water Temp Pro, Onset Co., Bourne, MA, USA) were installed at depths of 0, 2,4,6,8,10,12,14,16,18,21,24,27,30, and 33 m, and water temperature was measured at 10 min intervals. As both meteorological and hydrological data were needed to analyze the characteristics of the hydrodynamic mixing in the reservoir, data were collected from the Korea Meteorological Administration (KMA).…”
Section: Sampling and Analysismentioning
confidence: 99%
“…However, most of the reported carbon emission from reservoirs have been estimated using limited field data [5,23], for which the methodological and analytical uncertainties are quite high [6,24]. In particular, because carbon emissions from reservoir surface water vary widely over time and space [19,25], data measured at a specific time and place cannot represent overall CO 2 fluxes, which are very temporally and spatially dynamic [26,27]. In deep lakes and reservoirs, mixing occurs between the upper and lower layers when thermal stratification is destroyed, and the accumulated supersaturated CO 2 is spread to the surface layer.…”
Section: Introductionmentioning
confidence: 99%